Hubungan Pola Konsumsi Fastfood Dengan Kejadian Overweight Pada Remaja Putri Di SMA Batik 1 Surakarta - Putri, Leily Nurma; , Fitriana Mustikaningrum, S.Gz, M.Sc; , Dyah Widowati, SKM (2014)
Introduction : Overweightis often the case in big cities in Indonesia. Their teens are most often overweight. Teens more influencedby the environment, try new things one of which consume fastfood. Based on the initial survey that has been conducted, from 20 girls known 30% overweight student.The one that plays a role in the incidence of overweight is fast food consumption patterns. Excessive fast food consumption patterns will affect the prevalence of overweight. Destination :This study aims to determine the relationship of fast food consumption patterns with Genesis over weight in adolescent girls in SMA Batik 1 Surakarta. Research methods : The study was observational with cross sectional approach. The data was collected anthropometric measurements of weight and heightto determine the nutritional status of girls then performed fast food consumption pattern of the application form with in the last 1 month. The subjects used in this study were 40 female students who meet the criteria of Class XI, selected by proportional random sampling method. Chi-square analysisis used to determine the relationship of fast food consumption patterns with a high incidence of over weight in SMA Batik 1 Surakarta. Result :Young women in SMA Batik 1 Surakarta over weight of 47.5% and amounted to52.5% of normal. The frequency of fast food consumptionin the category of the most rare and very seldom with the same prevalence of 42.5%. The number of his many fast food consumption by 52.5% and amounted to47.5% slightly and results of Chi-square analysis p<0.05. Conclusions : There is a relationship between fast food consumption patterns (based on the frequency and amount of consumption) with the incidence of overweight in adolescent girls in SMA Batik 1 Surakarta.